REMODEL larger cohort with long‐term outcomes and meta‐analysis of standalone balloon dilation studies. (30th July 2015) - Chandra, Rakesh K.; Kern, Robert C.; Cutler, Jeffrey L.; Welch, Kevin C.; Russell, Paul T.
Abstract : Objectives/Hypothesis: To provide the final results from the REMODEL (randomized evaluation of maxillary antrostomy versus ostial dilation efficacy through long‐term follow‐up) full‐study cohorts and perform meta‐analyses of standalone balloon sinus dilation studies to explore long‐term outcomes in a large patient sample. Study Design: Randomized controlled trial and meta‐analysis. Methods: Final outcomes from the REMODEL randomized trial, including a larger cohort of 135 patients treated with functional endoscopic sinus surgery (FESS) or in‐office balloon dilation, were evaluated. One hundred thirty patients had 12‐month data, 66 had 18‐month data, and 25 had 24‐month data. In addition, a meta‐analysis evaluated outcomes from six studies including 358 standalone balloon dilation patients with up to 24 months follow‐up. Results: Outcomes out to 2 years from the REMODEL full‐study cohort are consistent with 6‐month and 12‐month outcomes. In the meta‐analysis of standalone balloon dilation studies, technical success is 97.5%, and mean 20‐item Sino‐Nasal Outcomes Test scores are significantly and clinically improved at all time points ( P < .0001). There are significant reductions ( P < .0001) in work/school days missed, homebound days, physician/nurse visits, acute infections, and antibiotic prescriptions. Mean recovery time is 1.4 days. Comparison of 12‐month symptom improvements and revision rates between the REMODEL FESS arm (n = 59), REMODEL balloon dilation arm (n = 71), and pooled single‐arm standalone balloon dilation studies (n = 243) demonstrated no statistical difference. Conclusions: All outcomes are comparable between FESS and balloon dilation at all time points from 6 months to 24 months. Balloon dilation produces faster recovery, less postoperative pain, and fewer debridements than FESS. There is significant, durable benefit in a large series of 358 patients undergoing standalone balloon dilation. Level of Evidence: 1b. Laryngoscope, 126:44–50, 2016